Antioxidant, metal-binding and DNA-damaging properties of flavonolignans: a joint experimental and computational highlight based on 7-O-galloylsilybin - Vacek, Jan; Zatloukalová, Martina; Desmier, Thomas; Nezhodová, Veronika; Hrbáč, Jan; Kubala, Martin; Křen, Vladimír; Ulrichová, Jitka; Trouillas, Patrick (Chemico-biological interactions, 2013)
Besides the well-known chemoprotective effects of polyphenols, their prooxidant activities via interactions with biomacromolecules as DNA and proteins are of the utmost importance. Current research focuses not only on natural polyphenols but also on synthetically prepared analogs with promising biological activities. In the present study, the antioxidant and prooxidant properties of a semi-synthetic flavonolignan 7-O-galloylsilybin (7-GSB) are described. The presence of the galloyl moiety significantly enhances the antioxidant capacity of 7-GSB compared to that of silybin (SB). These findings were supported by electrochemistry, DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity, total antioxidant capacity (CL-TAC) and DFT (density functional theory) calculations. A three-step oxidation mechanism of 7-GSB is proposed at pH 7.4, in which the galloyl moiety is first oxidized at Ep,1=+0.20V (vs. Ag/AgCl3M KCl) followed by oxidation of the 20-OH (Ep,2=+0.55V) and most probably 5-OH (Ep,3=+0.95V) group of SB moiety. The molecular orbital analysis and the calculation of O-H bond dissociation enthalpies (BDE) fully rationalize the electrooxidation processes. The metal (Cu(2+)) complexation of 7-GSB was studied, which appeared to involve both the galloyl moiety and the 5-OH group. The prooxidant effects of the metal-complexes were then studied according to their capacity to oxidatively induce DNA modification and cleavage. These results paved the way towards the conclusion that 7-O-galloyl substitution to SB concomitantly (i) enhances antioxidant (ROS scavenging) capacity and (ii) decreases prooxidant effect/DNA damage after Cu complexation. This multidisciplinary approach provides a comprehensive mechanistic picture of the antioxidant vs. metal-induced prooxidant effects of flavonolignans at the molecular level, under ex vivo conditions.
Keywords: DNA Damage; Antioxidants; Copper; Luminescent Measurements; Biphenyl Compounds; poškození DNA; DNA-damage; silymarin; měď; Flavonolignans; Spectrophotometry, Ultraviolet; Molecular Dynamics Simulation; Silymarin; bifenylové sloučeniny; antioxidancia; Albumin; Picrates; elektrochemické techniky; Electrochemical Techniques; Nucleic acids; simulace molekulární dynamiky; pikráty; luminiscenční měření; spektrofotometrie ultrafialová; Prooxidant effects